PERBANDINGAN METODE INKUIRI TERBIMBING DAN BEBAS TERMODIFIKASI TERHADAP MOTIVASI DAN HASIL BELAJAR - Kadek Budiasa; I Dewa Putu Nyeneng; Viyanti - (Jurnal Pembelajaran Fisika, 2013)
The purpose of this study to determine: (1) The average difference between the use of student motivation guided inquiry method with modified free inquiry method, (2) the average difference in student learning outcomes between the use of guided inquiry with the inquiry method freely modified. Population were all eighth grade students in the second semester in the SMP Negeri 1 Candipuro, while samples taken VIIId the class as a class using guided inquiry and VIIIe class as a class that uses a modified method of free inquiry. Sampling technique using cluster random sampling. The results from this research is: (1) There is a difference in mean average student motivation between the use of guided inquiry method with the modified method of free inquiry, (2) There is a difference in average student learning outcomes between the use of guided inquiry with modified method of free inquiry. The average value of learning outcomes in the classroom guided inquiry is 70.87 while in the class of non-modified inquiry is 66.21 and the average value of motivation in classroom guided inquiry is 69.57. while in the class of non-modified inquiry is 65.90. Keywords: Guided Inquiry, Modified Free Inquiry, Student Learning Outcomes, Student Motivation.